Develop a stepwise integrated method to screen biomarkers of Baihe‐Dihuang Tang on the treatment of depression in rats applying with composition screened, untargeted, and targeted metabolomics analysis. Issue 10 (10th March 2022) - Gu, Shuo; Mou, Tingting; Chen, Jian; Wang, Jing; Zhang, Ying; Cui, Meirong; Hao, Wenqian; Sun, Yue; Zhang, Chengqin; Zhao, Tiantian; Wei, Binbin
Abstract : Baihe‐Dihuang Tang is a commonly prescribed remedy for depression. In this study, component screening with untargeted and targeted metabolomics was used to identify potential biomarkers for depression in chronic unpredictable mildly stressed rats. Using this novel identification method, the screening of organic acids, lily saponins, iridoids, and other ingredients formed the basis for subsequent metabolomics research. Baihe‐Dihuang Tang supplementation in chronic unpredictable mild‐stress‐induced depression models, increased their body weight, sucrose preference, brain‐derived neurotrophic factor deposition, and spatial exploring. Untargeted metabolomics revealed that Baihe‐Dihuang Tang exerts its antidepressant effects by regulating the levels of lipids, organic acids, and its derivatives, and benzenoids in the brain, plasma, and urine of the depressed rats. Moreover, it also modulates the d ‐glutamine and d ‐glutamate metabolism and purine metabolism. Targeted metabolomics demonstrated significant reduction in l ‐glutamate levels in the brains of depressed rats. This could be a potential biomarker for depression. Baihe‐Dihuang Tang alleviated depression by regulating the levels of l ‐glutamate, xanthine, and adenine in the brains of depressed rats. Together, these findings conclusively established the promising therapeutic effect of Baihe‐Dihuang Tang on depression and also unraveled the underlying molecular mechanism of its potential antidepressant function.